Reproductive Biology of Osteochilus hasselti C.V from the Tarai River, Tarai Bangun Village, Tambang District, Kampar Regency, Riau Province - Ica Hayati; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTOsteochilus hasselti is found in the Tarai River that has been contaminated with organic pollution and it may affects the reproductive biology of the fish. A study aims to understand the reproductive biology of O. hasselti has been conducted. The fish was sampled 3 times, once/month, from November 2017 to January 2018. Parameters measured were sex ratio, gonad maturity level, Gonad Somatic Index (GSI), fecundity and egg diameter. Results shown that there was 29 males and 49 females (sex ratio 1:2). Male has slimmer body, brighter color than those of the female. Genital papilla of the male was white, while that of the female was red. Size at maturity level in male ranged from 95 to 170 mm SL, while that of the females was 90 to 190 mm SL. The average GSI of male ranged from 1.61 to 8.51% while that of the females was 1.02 to 11.14%. The average fecundity was 65,451 eggs/female and egg diameter was 0.10 to 1.00 mm. Based on the size of egg diameter can be concluded this fish is total spawner. Keywords: Sex ratio, gonad maturity level, gonad somatic index, fecundity, total spawner